Financial Stability and Early Warning Systems: Lessons for I.R. of Iran - Kazem Yavari (فصلنامه پژوهش‌های اقتصادی ایران, 2012)
The main purpose of this paper is to overview early warning systems, discussing their importance and relevance for current situations of Iran’s financial system and economy. An early warning system generates ex-ante warnings of potential problems that may emerge or develop in the future on account of the current risk profile of a financial institution. Although there are various approaches to model warning and prediction of financial and economic risks, the signal extraction approach is the most popular one and gained more attention than any other approaches by financial institutions and policy makers. This approach is explained in detail. The paper will also analyze importance and relevance of early warning systems for Iran’s financial system and economy. Pointing out to some leading indicators, the paper suggests that Iranian authorities and in particular economic policy makers need to develop and design an appropriate early warning system to be able to avoid future financial and economic crises or at least take necessary measures to reduce their negative impacts